Excavations at Sarachane in Istanbul, Volume 1. - Harrison, R. Martin.
1 online resource (550 pages)
Keywords: This work is the first volume of two that will be the full report of major excavations carried out by Dumbarton Oaks and the Istanbul Archaeological Museum at Sarachane in the heart of ancient Constantinople. This volume includes discussion of excavation and stratigraphy; catalogs of sculpture, revetment, mosaic, small finds and other materials: and general treatment of architecture, sculpture, and history of the site. Originally published in 1986. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.